History of Advocacy in Tribal Telephony and Telecommunications, 1980–2020 - Morris, Traci L. (The journal of community informatics, 2026)
The history of Tribal advocacy in telecommunications policy is remarkable, yet many people are unaware of it. On Tribal lands, the connectivity gap extends beyond just access to communication technologies, including basic telephone services and now broadband. This reveals deep structural inequalities caused by limited funding, inadequate physical infrastructure, ineffective policies, lack of data, and the government's failure to meet its trust responsibilities. This article provides a comprehensive timeline, organized by decade, of Tribal advocacy in the communications, telephony, and telecommunications sectors from 1980–2020. The article also provides an overview of Federal Communications Commission (FCC) dockets and proceedings, along with responses from Tribal Nations and Tribal organizations. This forty-year span, along with the years 2020–2025 (discussed in the next article), illustrates a body of policy that demonstrates Tribal Nations’ exercising self-determination rights as outlined in their trust relationship with the United States.